STIM1 and ORAI1 mutations leading to tubular aggregate myopathies are sensitive to the Store-operated Ca2+-entry modulators CIC-37 and CIC-39. (July 2022) - Riva, Beatrice; Pessolano, Emanuela; Quaglia, Edoardo; Cordero-Sanchez, Celia; Bhela, Irene P.; Topf, Ana; Serafini, Marta; Cox, Daniel; Harris, Elizabeth; Garibaldi, Matteo; Barresi, Rita; Pirali, Tracey; et al.
Highlights: STIM1 and ORAI1 gain-of-function mutations trigger tubular aggregate myopathies. These mutations lead to an increased basal Ca 2+ and store-operated Ca 2+ -entry. These mutations are sensitive to store-operated Ca 2+ -entry modulators. Abstract: Gain-of-function mutations on STIM1 and ORAI1 genes are responsible for an increased store-operated calcium entry, and underlie the characteristic symptoms of three overlapping ultra-rare genetic disorders ( i.e tubular aggregate myopathy, Stormorken syndrome, York platelet syndrome) that can be grouped as tubular aggregate myopathies. These mutations lead to a wide spectrum of defects, which usually include muscle weakness and cramps. Negative modulators of store-operated Ca 2+ -entry targeting wild-type STIM1 and ORAI1 have entered clinical trials for a different array of disorders, including pancreatitis, COVID-19, cancer, and autoimmune disorders and, while efficacy data is awaited, safety data indicates tolerability of this STIM1/ORAI1 mutations are amenable to pharmacological intervention. If this were so, given that there are no approved treatments or clinical trials ongoing for these rare disorders, it could be envisaged that these agents could also rehabilitate tubular aggregate myopathy patients. In the present contribution we characterized the Ca 2+ -entry patterns induced by eleven STIM1 and three ORAI1 mutations in heterologous systems or in patient-derived cells, i.e. fibroblasts and myotubes, and evaluated the effect of CIC-37 and CIC-39, two novel store-operated calcium entry modulators. Our data show that all STIM1 and ORAI1 gain-of-function mutations tested, with the possible exception of the R304Q STIM1 mutation, are amenable to inhibition, albeit with slightly different sensitivities, paving the way to the development of SOCE modulators in tubular aggregate myopathies. Graphical Abstract: Image, graphical abstract